New characteristics of Meiyu precipitation changes in the middle and lower reaches of the Yangtze River since 2000 - Hao, Li-Sheng; Ding, Yi-Hui; Liu, Yan-Ju (Frontiers in Climate, 2024)
This study comprehensively analyzed the long-term changes of Meiyu in the middle and lower reaches of the Yangtze River with regard to precipitation, precipitation threshold, and interdecadal changes in atmospheric circulation.Results revealed obvious new features of Meiyu precipitation since 2000. (1) Meiyu precipitation shows a significant linear increase trend, with an average increment of 73.5 mm every 10 years. The increase in torrential rain is the most significant, accounting for 61% of the total precipitation increase, and its proportion has been increasing, while the proportions of light, moderate, and heavy rain in the total precipitation have been decreasing. ( 2) At the interdecadal scale, Meiyu precipitation and the local surface average temperature show opposite changes. Meiyu precipitation decreases by approximately 150 mm for every 1°C increase in the average temperature. This inverse correlation was not evident before 2000. (3) The saturated specific humidity in this area shows a significant increasing trend, indicating that precipitation in this area is caused by a higher threshold of atmospheric saturation and condensation, which may be a reason for the low Meiyu precipitation during high-temperature years. (4) The main atmospheric circulation in East Asia associated with Meiyu shows clear interdecadal changes, including the Western North Pacific Subtropical High and South Asian High having become significantly stronger and having extended westward and eastward, respectively, thereby facilitating the occurrence and persistence of Meiyu precipitation. The atmospheric circulation patterns associated with Meiyu, such as the Western North Pacific Subtropical High and South Asian High, have more significant impacts on Meiyu precipitation.